A Cytokine cocktail augments the efficacy of adoptive NK-92 cell therapy against mouse xenografts of human cancer - Samara, P.; Skopeliti, M.; Tsiatas, M. L.; Georgaki, S.; Gouloumis, C.; Voelter, W.; Dimopoulos, A.-M.; Bamias, A.; Tsitsilonis, O.E. (Anticancer Research, 2016)
Background/Aim: Peripheral blood mononuclear cells (PBMCs) activated with immobilized monoclonal antibody against cluster of differentiation 3 (CD3) secrete cytokines in their culture supernatant (termed ACD3S). We examined the antitumor efficacy of ACD3S-activated NK-92 cells in vitro and in vivo. Materials and Methods: Interleukin (IL) 2-depleted NK-92 cells were reactivated with ACD3S, analyzed for their phenotype and tested for cytotoxicity, and perforin and interferon (IFN) production. Severe combined immunodeficient (SCID) mice xenografted with human melanoma and breast cancer cells were treated with ACD3S-activated NK-92 cells and tumor growth was monitored. Results: Brief activation of IL2-depleted NK-92 cells with ACD3S fully restored their in vitro cytotoxicity towards tumor cells. ACD3S-activated NK-92 cells were phenotypically similar to standard NK-92 cells, but exhibited prolonged cytotoxicity and produced higher levels of IFN. When adoptively transferred to tumor-bearing SCID mice, these cells retarded the growth of melanoma and breast tumors. Conclusion: Stimulation of NK-92 cells with ACD3S may be useful in clinical cancer therapy, as an alternative method for ex vivo natural killer cell activation.
Keywords: Conditioned medium; Cytotoxicity; NK-92; SCID mice